Satellite observations of CO2 from a highly elliptical orbit for studies of the Arctic and boreal carbon cycle. Issue 5 (6th March 2014) - Nassar, Ray; Sioris, Chris E.; Jones, Dylan B. A.; McConnell, John C.
Abstract Here we report on an observing system simulation experiment (OSSE) to compare the efficacy of near‐infrared satellite observations of CO2 from a highly elliptical orbit (HEO) and a low Earth orbit (LEO), for constraining Arctic and boreal CO2 sources and sinks. The carbon cycle at these latitudes (~50–90°N) is primarily driven by the boreal forests, but increasing anthropogenic activity and the effects of climate change such as thawing of permafrost throughout this region could also have an important role in the coming years. A HEO enables quasi‐geostationary observations of Earth's northern high latitudes, which are not observed from a geostationary orbit. The orbit and observing characteristics for the HEO mission are based on the Weather, Climate and Air quality (WCA) concept proposed for the Polar Communications and Weather (PCW) mission, while those for the LEO mission are based on the Greenhouse gases Observing Satellite (GOSAT). Two WCA instrument configurations were investigated. Adopting the Optimal configuration yielded an observation data set that gave annual Arctic and boreal regional terrestrial biospheric CO2 flux uncertainties an average of 30% lower than those from GOSAT, while a smaller instrument configuration resulted in uncertainties averaging 20% lower than those from GOSAT. For either WCA instrument configuration, much greater reductions in uncertainty occur for spring, summer, and autumn than for winter, with Optimal flux uncertainties for June–August nearly 50% lower than from GOSAT. These findings demonstrate that CO2 observations from HEO offer significant advantages over LEO for constraining CO2 fluxes from the Arctic and boreal regions.